Pre-Restoration Sediment Budget of a Tidally Restricted Estuary Reveals Potential for Landward Transport - Rachel M. Allen; Neil K. Ganju (Estuaries and Coasts, 2026)

FOLFIRINOX Pharmacodynamic Interactions in 2D and 3D Pancreatic Cancer Cell Cultures - Taylor J. Allen-Coyle; Jin Niu; Eva Welsch; Neil T. Conlon; Weylon Garner; Martin Clynes; Finbarr O’Sullivan; Robert M. Straubinger; Donald E. Mager; Sandra Roche (The AAPS Journal, 2022)
The multi-drug combination regime, FOLFIRINOX, is a standard of care chemotherapeutic therapy for pancreatic cancer patients. However, systematic evaluation of potential pharmacodynamic interactions among multi-drug therapy has not been reported previously. Here, pharmacodynamic interactions of the FOLFIRINOX agents (5-fluorouracil (5-FU), oxaliplatin (Oxa) and SN-38, the active metabolite of irinotecan) were assessed across a panel of primary and established pancreatic cancer cells. Inhibition of cell proliferation was quantified for each drug, alone and in combination, to obtain quantitative, drug-specific interaction parameters and assess the nature of drug interactions. The experimental data were analysed assuming Bliss independent interactions, and nonlinear regression model fitting was conducted in SAS. Estimates of the drug interaction term, psi (ψ), revealed that the Oxa/SN-38 combination appeared synergistic in PANC-1 (ψ = 0.6, 95% CI = 0.4, 0.9) and modestly synergistic, close to additive, in MIAPaCa-2 (ψ = 0.8, 95% CI = 0.6, 1.0) in 2D assays. The triple combination was strongly synergistic in MIAPaCa-2 (ψ = 0.2, 95% CI = 0.1, 0.3) and modestly synergistic/borderline additive in PANC-1 2D (ψ = 0.8, 95% CI = 0.6, 1.0). The triple combination showed antagonistic interactions in the primary PIN-127 and 3D PANC-1 model (ψ > 1). Quantitative pharmacodynamic interactions have not been described for the FOLFIRINOX regimen; this analysis suggests a complex interplay among the three chemotherapeutic agents. Extension of this pharmacodynamic analysis approach to clinical/translational studies of the FOLFIRINOX combination could reveal additional pharmacodynamic interactions and guide further refinement of this regimen to achieve optimal clinical responses. Graphical abstract

A stochastic model for estimating sustainable limits to wildlife mortality in a changing world - Oliver Manlik; Robert C. Lacy; William B. Sherwin; Hugh Finn; Neil R. Loneragan; Simon J. Allen (Conservation Biology, 2022)
Human‐caused mortality of wildlife is a pervasive threat to biodiversity. Assessing the population‐level impact of fisheries bycatch and other human‐caused mortality of wildlife has typically relied upon deterministic methods. However, population declines are often accelerated by stochastic factors that are not accounted for in such conventional methods. Building on the widely applied potential biological removal (PBR) equation, we devised a new population modeling approach for estimating sustainable limits to human‐caused mortality and applied it in a case study of bottlenose dolphins affected by capture in an Australian demersal otter trawl fishery. Our approach, termed sustainable anthropogenic mortality in stochastic environments (SAMSE), incorporates environmental and demographic stochasticity, including the dependency of offspring on their mothers. The SAMSE limit is the maximum number of individuals that can be removed without causing negative stochastic population growth. We calculated a PBR of 16.2 dolphins per year based on the best abundance estimate available. In contrast, the SAMSE model indicated that only 2.3–8.0 dolphins could be removed annually without causing a population decline in a stochastic environment. These results suggest that reported bycatch rates are unsustainable in the long term, unless reproductive rates are consistently higher than average. The difference between the deterministic PBR calculation and the SAMSE limits showed that deterministic approaches may underestimate the true impact of human‐caused mortality of wildlife. This highlights the importance of integrating stochasticity when evaluating the impact of bycatch or other human‐caused mortality on wildlife, such as hunting, lethal control measures, and wind turbine collisions. Although population viability analysis (PVA) has been used to evaluate the impact of human‐caused mortality, SAMSE represents a novel PVA framework that incorporates stochasticity for estimating acceptable levels of human‐caused mortality. It offers a broadly applicable, stochastic addition to the demographic toolbox to evaluate the impact of human‐caused mortality on wildlife.

Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark ( Sphyrna lewini ) - James M. Anderson; Patrick T. Rex; Kelsey Maloney; Mark Johnston; Deron Verbeck; Neil Allen; Kim Holland (Journal of Fish Biology, 2022)
A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.

Interplays between changing biophysical and social dynamics under climate change: Implications for limits to sustainable adaptation in food systems - Rachel Bezner Kerr; Lars Otto Naess; Bridget Allen‐O’Neil; Edmond Totin; Hanson Nyantakyi‐Frimpong; Camilla Risvoll; Marta G. Rivera Ferre; Feliu López‐i‐Gelats; Siri Eriksen (Global Change Biology, 2022)
Climate change scenarios have significant implications for the livelihoods and food security of particular groups in society and will necessitate a range of adaptation actions. While there is a significant literature on the social as well as biophysical factors and limits to adaptation, less is known about the interactions between these, and what such interactions mean for the prospects of achieving sustainable and resilient food systems. This paper is an attempt at addressing this gap by examining changing biophysical and social factors, with specific consideration of vulnerable groups, across four case studies (Ghana, Malawi, Norway and Spain). In each case, future climate change scenarios and associated biophysical limits are mapped onto four key social factors that drive vulnerability and mediate adaptation, namely, scale, history, power and politics, and social differentiation. We then consider what the interaction between biophysical limits and socio‐political dynamics means for the options for and limits to future adaptation, and how climate may interact with, and reshape, socio‐political elements. We find that biophysical limits and socio‐political factors do not operate in isolation, but interact, with dynamic relationships determining the ‘space’ or set of options for sustainable adaptation. By connecting the perspectives of biophysical and social factors, the study illuminates the risks of unanticipated outcomes that result from the disregard of local contexts in the implementation of adaptation measures. We conclude that a framework focusing on the space for sustainable adaptation conditioned by biophysical and social factors, and their interactions, can help provide evidence on what does and does not constitute sustainable adaptation, and help to counter unhelpful narratives of climate change as a sole or dominant cause of challenges in food systems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Assessing mid-latitude dynamics in extreme event attribution systems - Daniel Mitchell; Paolo Davini; Ben Harvey; Neil Massey; Karsten Haustein; Tim Woollings; Richard Jones; Fredi Otto; Benoit Guillod; Sarah Sparrow; David Wallom; Myles Allen (Climate Dynamics, 2017)

Seasonal spatial patterns of projected anthropogenic warming in complex terrain: a modeling study of the western US - David E. Rupp; Sihan Li; Philip W. Mote; Karen M. Shell; Neil Massey; Sarah N. Sparrow; David C. H. Wallom; Myles R. Allen (Climate Dynamics, 2017)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Genetic isolation between coastal and fishery‐impacted, offshore bottlenose dolphin ( Tursiops spp.) populations - Simon J. Allen; Kate A. Bryant; Robert H. S. Kraus; Neil R. Loneragan; Anna M. Kopps; Alexander M. Brown; Livia Gerber; Michael Krützen (Molecular Ecology, 2016)
The identification of species and population boundaries is important in both evolutionary and conservation biology. In recent years, new population genetic and computational methods for estimating population parameters and testing hypotheses in a quantitative manner have emerged. Using a Bayesian framework and a quantitative model‐testing approach, we evaluated the species status and genetic connectedness of bottlenose dolphin ( Tursiops spp.) populations off remote northwestern Australia, with a focus on pelagic ‘offshore’ dolphins subject to incidental capture in a trawl fishery. We analysed 71 dolphin samples from three sites beyond the 50 m depth contour (the inshore boundary of the fishery) and up to 170 km offshore, including incidentally caught and free‐ranging individuals associating with trawl vessels, and 273 dolphins sampled at 12 coastal sites inshore of the 50 m depth contour and within 10 km of the coast. Results from 19 nuclear microsatellite markers showed significant population structure between dolphins from within the fishery and coastal sites, but also among dolphins from coastal sites, identifying three coastal populations. Moreover, we found no current or historic gene flow into the offshore population in the region of the fishery, indicating a complete lack of recruitment from coastal sites. Mitochondrial DNA corroborated our findings of genetic isolation between dolphins from the offshore population and coastal sites. Most offshore individuals formed a monophyletic clade with common bottlenose dolphins ( T. truncatus ), while all 273 individuals sampled coastally formed a well‐supported clade of Indo‐Pacific bottlenose dolphins ( T. aduncus ). By including a quantitative modelling approach, our study explicitly took evolutionary processes into account for informing the conservation and management of protected species. As such, it may serve as a template for other, similarly inaccessible study populations.

Climate change, climate justice and the application of probabilistic event attribution to summer heat extremes in the California Central Valley - Roberto Mera; Neil Massey; David E. Rupp; Philip Mote; Myles Allen; Peter C. Frumhoff (Climatic Change, 2015)

Attribution analysis of high precipitation events in summer in England and Wales over the last decade - Friederike E. L. Otto; Suzanne M. Rosier; Myles R. Allen; Neil R. Massey; Cameron J. Rye; Jara Imbers Quintana (Climatic Change, 2015)

The evolution of authigenic Zn–Pb–Fe-bearing phases in the Grieves Siding peat, western Tasmania - Richelle Awid-Pascual; Vadim S. Kamenetsky; Karsten Goemann; Neil Allen; Taryn L. Noble; Bernd G. Lottermoser; Thomas Rodemann (Contributions to Mineralogy and Petrology, 2015)

Heterogeneity of Mitral Leaflet Matrix Composition and Turnover Correlates with Regional Leaflet Strain - Elizabeth H. Stephens; Patrick S. Connell; Monica M. Fahrenholtz; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Cellular and Extracellular Matrix Basis for Heterogeneity in Mitral Annular Contraction - Elizabeth H. Stephens; Monica M. Fahrenholtz; Patrick S. Connell; Tomasz A. Timek; George T. Daughters; Joyce J. Kuo; Aaron M. Patton; Neil B. Ingels; D. Craig Miller; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2015)

Subsurface behavior of bottlenose dolphins ( Tursiops truncatus ) interacting with fish trawl nets in northwestern Australia: Implications for bycatch mitigation - Vanessa F. Jaiteh; Simon J. Allen; Jessica J. Meeuwig; Neil R. Loneragan (Marine Mammal Science, 2013)
Most studies of delphinid‐trawler interactions have documented the surface behavior of dolphins feeding on discarded bycatch, but not their subsurface behavior around demersal trawl gear. Using video cameras mounted inside trawl nets, we recorded the subsurface behavior of common bottlenose dolphins ( Tursiops truncatus ) in a demersal fish trawl fishery in northwestern Australia. Footage from 36 trawls across the fishery was analyzed to determine the extent of dolphin‐gear interactions and the behavior of dolphins inside the nets. Interaction rates were high, with dolphins present inside and outside the nets during 29 and 34 trawls, respectively, and for up to 99% of the trawl duration. The proportion of foraging behaviors exhibited inside the nets was higher than the proportions of traveling and socializing behaviors. Twenty‐nine individuals were identified inside the net, seven of which returned repeatedly within and between trawls and fishing trips, but were observed primarily in the same localized areas in which they were first recorded. Our results suggest that entering trawl nets may be a frequently occurring, yet specialized behavior exhibited by a small subset of trawler‐associated dolphins. We propose that gear modifications, not spatial or temporal adjustments to fishing effort, have the greatest potential to reduce dolphin bycatch.

Retrospective assessment of dryland soil stability in relation to grazing and climate change - Robert A. Washington-Allen; Neil E. West; R. Douglas Ramsey; Debra H. Phillips; Herman H. Shugart (Environmental Monitoring and Assessment, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Auxin cross-talk: integration of signalling pathways to control plant development - Ranjan Swarup; Geraint Parry; Neil Graham; Trudie Allen; Malcolm Bennett (Plant Molecular Biology, 2002)

Quick on the Uptake: Characterization of a Family of Plant Auxin Influx Carriers - Geraint Parry; Alan Marchant; Sean May; Ranjan Swarup; Kamal Swarup; Nick James; Neil Graham; Trudie Allen; Tony Martucci; Antony Yemm; Richard Napier; Ken Manning; et al. (Journal of Plant Growth Regulation, 2001)

Forestry for Sustainable Development: Making It Happen - Hans Gregersen; Allen Lundgren; Neil Byron (Journal of Forestry, 1998)
Sustainable development is a process of meeting the continuing, evolving needs of people while protecting and enhancing the resource base on which all production of goods and environmental services depends. Good forest management is an essential part of the sustainable development process. Given the need to share the benefits from forests, and given the uncertainty we face concerning the future, a participatory adaptive management approach is needed, one that lets us most easily adapt if we find in the future that we are on a path of unsustainable development.